Gliflozins, a new hope for heart failure? systematic review - Golin Brustolin, Ana Beatriz; Porcile, Rafael (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Background: Heart Failure (HF) is a public health problem with high morbidity and mortality rates, as well as resource consumption. Sodium-glucose cotransporter type 2 inhibitors (SGLT-2 inhibitors), originally developed for type 2 diabetes, have become an attractive therapeutic option for HF. Recent studies have shown that gliflozins, a type of SGLT-2 inhibitor, reduce the risk of cardiovascular death and hospitalization for HF compared to placebo. Further studies are needed to confirm these findings and establish their place in the current therapy for HF. Material and methods: A systematic review of studies published in PUBMED evaluating the use of gliflozins, a subtype of InSGLT-2, in patients with heart failure was performed. Results: Based on the articles analyzed, a total of 25,960 patients with heart failure were included, who were studied in 4 different studies. Conclusion: The use of gliflozins in patients with heart failure was found to be associated with a significant reduction in the risk of cardiovascular death, hospitalization for heart failure, and adverse cardiovascular events compared with placebo